Influence of Chlorhexidine and Cetylpyridine on Periodontal Status and Indicators of Oxidative Stress in Patients with Type 1 Diabetes - Jakub Lipski; Anna Duda-Sobczak; Marta Napierala; Ewa Florek; Dorota Zozulinska-Ziolkiewicz; Marzena Wyganowska-Swiatkowska (MDPI AG, 2021)
Objective: One of the treatment goals in type 1 diabetes and periodontitis is to address chronic inflammation to prevent the development of neurovascular complications. The aim of this study was to assess the local anti-inflammatory effects of chlorhexidine digluconate and cetylpyridine chloride on periodontal status and indicators of oxidative stress in saliva in patients with type 1 diabetes. Materials and Methods: A total of 42 subjects aged 27 (interquartile range, IQR 22-35) years, with type 1 diabetes for a duration of 12 (IQR 9-18) years, and glycated hemoglobin 8.05 (IQR 7.1-9.4)% were included. Patients were examined twice-initially, and after 14 days of using toothpaste with chlorhexidine and cetylpyridine. Clinical examination of gingival tissues was performed. Certain oxidative stress markers (TP, TEAC, TBARS, AOPP) were measured in the saliva samples. Results: There were significant changes in clinical indicators of periodontal status before and after the application of the toothpaste (API before 0.35 (0.24-0.65) vs. API after 0.265 (0.18-0.39), p = 0.03; SBI before 0.07 (0.04-0.15) vs. SBI after 0.035 (0-0.06), p = 0.002; GI before 0.88 (0.46-1) vs. GI after 0.67 (0.25-1), p = 0.0008). The concentration of saliva TBARS decreased (p = 0.00005) and TEAC increased (p = 0.09). Conclusion: Proper oral hygiene supported by antibacterial chemicals may improve the periodontal status and reduce inflammation.